Advances in FDTD computational electrodynamics photonics and nanotechnology - Taflove, Allen; Oskooi, Ardavan; Johnson, Steven G. (Artech House antennas and propagation series, 2013)
This book presents the current state-of-the-art in formulating and implementing computational models of light with materials such as silicon and gold at the nanoscale. Maxwell's equations are solved using the finite-difference time-domain (FDTD) technique. It will help you understand the latest developments in computational modeling of nanoscale optical microscopy and microchip lithography.